(untitled) (Journal of Humanities & Social Science (JHSS), 2023)
The transition from colonialism to independence and Ujamaa had great impacts on society—politically, economically and socially. This is discussed in relation to the novel Village in Uhuru (1969) by Gabriel Ruhumbika. Within the backdrop of independence, he explores the social changes that occur in the small village of Chamambo. Through two main characters—namely Balinde and Musilanga—Ruhumbika explores the changing social values. This paper argues that masculinity is a social construct. It will explore how Musilanga serves as a representative of hegemonic masculinity, and how through the actions of his son, he is deprived of this designation, leaving a void which remains to be filled.